Good for patients but not learners? Exploring faculty and learner virtual care integration. Issue 12 (1st July 2022) - Shepherd, Lisa; McConnell, Allison; Watling, Christopher
Abstract: Background: The pandemic catapulted the adoption of virtual care far ahead of its anticipated maturation date, forcing faculty to role model and teach learners with barely enough time to master it themselves. With a scant body of prepandemic literature now accompanied by experience gained under extraordinary circumstances, we can benefit from understanding ad hoc strategies implemented by those on the front lines and from listening to learners about what is working and what is not. The purpose of this study was to explore the experience of learner integration into virtual care from both the faculty and learner perspectives. Methods: Using a constructivist grounded theory methodology and sociomateriality as a sensitising concept, we recruited participants using purposeful and theoretical sampling from a Canadian University with limited prepandemic virtual care provision. We interviewed 16 faculty and 5 learners spanning a breadth of specialties and years of practice/education to probe their experience of teaching and learning virtual care. Data collection and analysis were conducted iteratively with themes identified through constant comparative analysis. Results: Integrating learners into virtual care proved challenging initially because of a lack of familiarity with the process and later because of disrupted workflow, triggered by the structure and logistics of the virtual care clinic. Both faculty and learners identified learning deficiencies in the virtual care experience when compared with in‐person clinics, but several unique and valuable learning affordances were noted. All faculty expressed a desire to keep virtual care as part of their future clinic practice, but paradoxically most felt that they were unlikely to include learners. Conclusions: Training learners in virtual care is an educational challenge that will not disappear with COVID‐19, even if our participants wished it could. The perceived value for patients but not learners begs a reconsideration of the sociomaterial contribution to this pandemic paradox. Abstract : Paradoxically, virtual care is found to be valued for patients but not for the learners who need to care for those patients. This article explores the perception that virtual care settings offer inferior learning experiences.